Boosting Productivity in Sub-Saharan Africa : Policies and Institutions to Promote Efficiency - Calderon, Cesar (Washington, DC: World Bank, 2022)
This book documents the productivity trends in Sub-Saharan Africa in three different dimensions, assessing productivity at the aggregate level, the sectoral level, and the establishment level. It characterizes the evolution of productivity in the region relative to other countries and regions, as well as country groups in Africa, classified by their degree of natural resource abundance and condition of fragility. The volume suggests that the persistence of the productivity gap in Africa vis-à-vis the technological frontier can be attributed to the slow accumulation of physical and human capital relative to the region’s growing population, as well as the poor allocation of these resources. These allocative inefficiencies are the outcome of policies and institutions that introduce distortions in the decision-making process of individuals. Hence, the volume assesses the implications of production decisions across agricultural farms and manufacturing firms. It presents evidence on aggregate productivity from the perspective of production units, using recent household surveys for farmers and firm-level surveys for select countries, as well as frontier estimation techniques. It documents the extent of severe resource misallocation across agricultural and manufacturing production units. These distortions decelerate the growth of the production units, disincentivize their adoption of productivity-enhancing technologies, and reduce the ability of their peers to learn new techniques. Boosting Productivity in Sub-Saharan Africa highlights the adoption of digital technologies to reduce some of these market frictions. Mobile money has increased financial inclusion in several countries, and digital financial technologies have given individuals access to savings instruments and loan products. Enhancing access to credit can help individuals invest in schooling and overcome the costs of formality. The volume discusses further avenues of research that may provide additional insights on the productivity dynamics across countries in the region, and it identifies the different channels of policy transmission to enhance productivity. The empirical work presented can help to guide the design of policy in the region.